One Little Mistake - Curtis, Emma (London Black Swan, 2017)
You trusted your best friend.... You shouldn't have. Vicky Seagrave is blessed: three beautiful children, a successful, doting husband, great friends and a job she loves. She should be perfectly happy. When she makes a split-second decision that risks everything she holds dear, there's only person she trusts enough to turn to. But Vicky is about to learn that one mistake is all it takes - that if you're careless with those you love, you don't deserve to keep them
Keywords: Best friends -- Secrecy -- Families